Iluminação nas áreas de hall e circulação de Shopping Center : Maceió Shopping, um estudo de caso. - Souza, Ellen Priscila Nunes de (2010)
This paper discusses the importance and quality of lighting, whether artificial or natural, visual comfort of commercial spaces. The growing importance of shopping centers has made one of its internal areas also stand out: the area intended for hall and circulation, which now is moving beyond the role of rest area. It comes, therefore, a diagnosis of performance in the areas of light and movement hall of a shopping center, located in the city of Maceió / AL, with regard to human needs (visibility and task performance) and architecture. To this end, two major methodological steps have been demarcated. The first step referring to the qualitative assessment by physical survey of the halls and circulation to characterize the system of lighting. The second step is the quantitative evaluation in a sample space and measurement of illuminance second NBR 5382 - Verificação de Iluminâncias de Interiores for artificial lighting systems with posterior simulation for daylighting system and compare the levels found and claimed by the NBR 5413 Iluminância de Interiores and the Building Code and the City of Maceió, municipal law No 5593/2007. These data were crossed resulting in a treatment situation of the lighting at the mall chosen in order: (i) general, where failures were observed in the distribution and height of elements that contribute to the process of reflection of light (natural and artificial) in internal space, and (ii) specific, and there are insufficient Illuminances to the implementation of the planned activities, movement and rest by the mapping curve isolux being situated in two selected sites. There have been made some conclusions in how the daylighting is obtained by first and second floors: the first has Illuminances below the standard in the three simulated points, even at the point below the opening zenith, their highest values ranging from 50lx and 300lx, the second Illuminances has at least four times higher than the values required in the three simulated points, yielding values ranging from 500lx and 7000lx.